KOMUNIKASI INTRABUDAYA DALAM UPACARA PERNIKAHAN ADAT BATAK TOBA SAMOSIR DI KABUPATEN KUANTAN SINGINGI - Sidabutar Sidabutar; Welly Wirman, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The wedding ceremony of Batak Toba Samosir currently has been going through a lot of shifting. One of the cause was the displacement the community to the new place, which need to adjust of new place. The research objective was to know the process and the intra culture of the wedding ceremony in Kuantan Singingi. This research used a qualitative descriptif in order to know the communication prosess and intra culture of the wedding Batak Toba Samosir. In this case, there were ten informants consisted of a head of the coustom, four mediators, four parents of the bride, and a leader of Batak Toba Samosir community. This research was done in Kuantan Singingi. The research show that there were some shifts on the wedding Batak Toba Samosir in Kuantan Singingi, namely Mebat or Paulak Une which was the first meet both of bride who accompanied by the parents of the groom to the bride parents' house, this event was held one week after the wedding, but in Kuantan Singingi this event was done after the wedding shorten the time. Maningkir Tangga was the ceremony where the bride's parents went to visit the groom’s house, while they where eat together and do jambar event. Batak Toba Samosir a wedding ceremony held at the groom or the bride’s house while in Kuantan Singingi it be held in the meeting hall as sopo Godang, in church yard. Generally, after the event of Martumpol (Marpadan) then both of bride return to their home and in this case they didn’t talk abaut the dowry at that time. In Kuantan Singingi, after the event of martumpol finished then it continved by eating on the groom’s house and it attendid both of the bride. The events of marsibuah-buahi conducted in the home twon before the wedding carried out. Early in the morning before went to the church, the bride brought dish of gold fish where the party conducted and each bride’s parents turns to feeding the bride in their home and then eat together. In Kuantan Singingi the event marsibuah-buahi conducted at the center of party. The factors that coused some shifts on the wedding ceremony of Batak Toba Samosir Kuantan Singingi such as the eficiency ot time, economic, and the development of the times. Keywords : Intra Culture, Comunication, Wedding Ceremony, Batak Toba Samosir Kuantan Singingi